Introductory econometrics : a modern approach - Wooldridge, Jeffrey M., 1960- (Australia ; Brazil ; Canada ; Mexico ; Singapore ; United Kingdom ; United States : Cengage, 2025)
Introductory Econometrics: A Modern Approach provides students with an understanding of how econometrics can answer questions in business, policy evaluation, and forecasting. Wooldridge’s practical approach emphasizes real-world applications and helps students develop the skills to interpret and apply econometric results. The 8th edition includes refined coverage of recent developments in the field, new examples, and online resources for hands-on practice.
Učebnice moderní ekonometrie zaměřená na praktické aplikace regresní analýzy a ekonometrických modelů. Autor přehledně vysvětluje teoretické základy i postupy analýzy dat, s důrazem na interpretaci výsledků a řešení reálných ekonomických problémů.
Terminologický slovník
Obsahuje bibliografické odkazy a rejstřík
Keywords: ekonometrické modely; ekonometrie; regresní analýza; učebnice; econometric models; econometrics; regression analysis; textbooks